Therapeutic plasma exchange followed by convalescent plasma transfusion in critical COVID-19—An exploratory study - Jaiswal, Vinod (Int J Infect Dis, 2021)
The pathophysiology of severe coronavirus disease 2019 (COVID-19) is primarily a host immune interplay to virus invasion. The therapeutic options have been explored either against hyperinflammation from dysregulated adaptive immunity or direct virus neutralization using antibodies from convalescent plasma (CP) of a recovered patient. The therapeutic plasma exchange (TPE) for removal of excessive inflammatory cytokines has been tried with success in COVID-19. We undertook this exploratory study to evaluate safety and efficacy of TPE followed by CP transfusion in 14 patients with critical COVID-19 requiring invasive mechanical ventilation (IMV). All patients showed improvement in symptoms and decrease of inflammatory markers especially CRP (p = 0.03). 10 patients were liberated from IMV after a median of 5.5 (3–36) days, post sequential therapy. Day 7 and Day 28 mortality was 21.4% and 28.6% respectively. The median duration ICU and hospital LOS were 12 (5−42) days and 18 (12−47) days respectively. No patient developed transfusion-associated complications, but three patients developed secondary bacterial sepsis within 14 days of therapy, and one died. This case series demonstrated the sequential use of TPE followed by CP transfusion as a therapeutic option in critical COVID-19.